PERANAN SEKTOR PERTANIAN DALAM PENYERAPAN TENAGA KERJA DI KABUPATEN TIMOR TENGAH UTARA - Khristina Kiha, Emilia; nuddin, Burha (EDUTECH CONSULTANT, 2019)
The aims of this research are to know how agricultural sector able to take the role in labour absorbtion in North Central Timor Regency, to know its regional development components during 2013 until 2017 and to project the amount of work opportunity in agricultural sector in North Central Timor Regency at ten years forwards, that is 2018 until 2027. The level of agricultural sector role in absorbtion of labour in regency North Central Timor between year 2013 up to year 2017 experiencing of degradation, While in the year 2014 experiencing of improvement and back experience of degradation in the year here in after that is year 2015 and year 2016. Condition of employment growth in agricultural sector of North Central Timor Regency is in a fast group with the net friction value is 3.125,61. By the fixed economic growth assumption 0,14557677 while the amount of resident is continusly increase, in 2017 the increase of employment in agricultural sector would be happened equal to 41.305 or a number of 4.130 per annum during the year of 2018 until 2027